Compound 21 Attenuates Isoflurane-Induced Injury in Neonatal Rat Hippocampal Neurons and Primary Rat Neuronal Cells by Upregulating METTL3 - Shen Y; Wu Y; Zhuang H; Chen Z; Zhang Q; Li P; Wang J; Huang Z; Zeng Q (Dove Medical Press, 2024)
Yaping Shen,1,2,* Yijiu Wu,3,* Hai Zhuang,4 Zhumei Chen,5 Qiong Zhang,5 Peixin Li,5 Jing Wang,3 Zhi Huang,1 Qingfan Zeng3,5 1Department of Interventional Radiology, The Affiliated Hospital of Guizhou Medical University, Guiyang, 550002, People's Republic of China; 2Department of Interventional Radiology, The Baiyun Hospital Affiliated to Guizhou Medical University, Guiyang, Guizhou, 550014, People's Republic of China; 3College of Anesthesiology, Guizhou Medical University, Guiyang, 550002, People's Republic of China; 4Department of Infectious, The Baiyun Hospital Affiliated to Guizhou Medical University, Guiyang, Guizhou, 550014, People's Republic of China; 5Department of Anesthesiology, The Baiyun Hospital Affiliated to Guizhou Medical University, Guiyang, Guizhou, 550014, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhi Huang, Department of interventional radiology, the Affiliated Hospital of Guizhou Medical University, Guiyang, 550002, People's Republic of China, Email huangzhi@gmc.edu.cn Qingfan Zeng, Department of Anesthesiology, The Baiyun Hospital Affiliated to Guizhou Medical University, Guiyang, Guizhou, 550014, People's Republic of China, Email 445483296@qq.comBackground: Isoflurane, as an anesthetic drug, has a neurotoxic effect on the developing brain tissue. Compound 21 (C21) has been reported to be neuroprotective and ameliorate stroke effects. However, the mechanism by which C21 protects against nerve damage remains unclear.Methods: Animal and cellular models of brain injury were constructed using isoflurane (ISO) in neonatal SD rats and primary rat neuronal cells (PRNCs). After treatment with C21, the ultrastructure and morphology of the hippocampus in the model rats were assessed using the transmission electron microscope and H&E staining. Methylation or apoptosis-related genes or proteins were examined using immunohistochemistry, RT-qPCR, and Western blot. The levels of inflammatory factors were monitored using the ELISA kits. m6A modification was analyzed by Dot blot and MeRIP-qPCR. Cell proliferation and apoptosis were also tested using Edu and TUNEL staining.Results: C21 suppresses apoptosis and inflammation and improves hippocampal morphology in ISO-induced neonatal rats. Mechanistically, C21 upregulates m6A modification, PPAR-a, BCL-2, and METTL3 in ISO-induced neonatal rats and ISO-treated PRNCs. C21 promotes cell proliferation, enhances BCL-2 m6A modification, and reduces inflammation by upregulating METTL3 by upregulating METTL3 in ISO-treated PRNCs.Conclusion: These findings suggest that C21 enhances neuronal cell survival and morphology and up-regulates methylation and Bc1-2 levels, potentially offering a therapeutic strategy for neuroprotection in clinical settings, particularly in cases of neurotoxic exposure. The mechanism may be related to the upregulation of METTL3. Keywords: compound 21, isoflurane, METTL3, anesthesia, neuron